PENGEMBANGAN SISTEM RESERVASI LAPANGAN BADMINTON BERBASIS WEB MENGGUNAKAN METODE AGILE UNTUK MENINGKATKAN EFISIENSI PROSES PEMESANAN - Sendy Bahri; Afrizal Zulmi Ramadan; Ahmad Zainul Arifin; Roeslan Djutalov (Journal of Research and Publication Innovation, 2025)
This paper presents the design and implementation of a web-based badminton court reservation system using the Agile methodology. The system aims to enhance the efficiency of the booking process by allowing users to reserve courts online, replacing the traditional manual method, which was time-consuming and error-prone. The Agile approach offers flexibility in system development through iterative processes and continuous evaluation, enabling developers to adapt to users' dynamic needs. Key features of the system include user registration, court scheduling, online payment, and user and schedule management. The system benefits administrators by streamlining data organization, reducing manual tasks, and improving scheduling accuracy. However, the system has some areas for improvement, including automatic schedule reminders, integration of diverse payment methods, and enhanced data security to ensure a better user experience. This study suggests further development to address these issues and maintain the system's relevance to user demands.